The Peaceful Policy of the Achaemenids in Egypt during the Years (525 - 486 BC) - Al-Noori, Maytham Abdul Kadim Jawad (Al-Adab Journal, 2020)
The excellent geographical location and famous ancient civilization that Egypt has urges the Persian kings, especially Achaemenids, to look at it a covetous and aspirant look to put it under their authority. Korsh II (559-529 BC) is the first one who looks and prepares for doing that, but death prohibits implementing his will. The king Kambiz (529-521 BC), who can fulfil his father’s dream about the culture and resources of this country in 525 BC, is influenced and feels proud of seeing himself crowned as a king in the Egyptian way. To satisfy and win Egyptians to his side, he follows his father’s policy of moderation principle and respecting the doctrines of the nations under his empire, and permits them to maintain their political and cultural entity and their own regulation. In his reign, Egyptians enjoy peace and tranquillity, and this is what the Egyptian texts assure. His successor, the king Dara I (521-486 BC), follows his steps. Dara’s reign is characterised to be a golden reign for Egypt. What he does in all respects, his indulgent treatment, his respect for the customs and traditions as well as the rituals and values, and giving full freedom to practise religious rites, make Egyptians feel content, thus, they regard the king Dara as one of their great Pharaohs and remain faithful for him till almost the end of his rule.